Sizing up gender: Bringing the joy of fat, gender and fashion into focus. Issue 2 (1st December 2021) - Evans, Calla; Stricke, Mindy; Barry, Ben; Friedman, May
This photo essay explores the intersections of gender, fatness and fashion through an innovative and evocative arts-based methodology involving collaboratively constructed macro, or close-up, photographs, portraits and garment images. With these images, we can examine people's experiences at the intersections of fat and gender through one of the most visible and embodied ways by which we construct and resist dominant narratives about these subject positions: fashion and self-fashioning. The Sizing Up Gender project engaged twelve self-identified cis-gender, trans, non-binary and two-spirit fat people across diverse race, class and other subject positions. Their narratives disrupt many dominant understandings of fat bodies and fashion and introduce a joyfulness to the story of dressing fat bodies that has been sorely neglected. We connect these feelings of joy to the concept of fabulousness, and consider how our participants' experiences of joy and risk are not only due to genders, races and sexualities but also to how these identities intersect with their fat embodiments, fatphobia and weight stigma. The images presented here, particularly the macro photographs, force us to look more closely at the subject matter at hand and introduce a visual fabulousness of their own, a fabulousness that is rarely afforded to fat bodies.